2014
DOI: 10.1007/s12402-014-0149-7
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body vibration improves cognitive functions of an adult with ADHD

Abstract: Adult attention deficit hyperactivity disorder (ADHD) is associated with a variety of cognitive impairments, which were shown to affect academic achievement and quality of life. Current treatment strategies, such as stimulant drug treatment, were demonstrated to effectively improve cognitive functions of patients with ADHD. However, most treatment strategies are associated with a number of disadvantages in a considerable proportion of patients, such as unsatisfactory effects, adverse clinical side effects or h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 41 publications
3
27
1
Order By: Relevance
“…The main aim of the present study is to examine whether WBV has acute effects on cognition, more specifically inhibition, on healthy 8–13 year-old children. This study replicates and extends previous studies describing positive effects of WBV on cognition in healthy adults [ 1 , 13 , 15 ]. Based on previous findings, it is expected that cognitive functioning improves in healthy children when assessed immediately following WBV treatment.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…The main aim of the present study is to examine whether WBV has acute effects on cognition, more specifically inhibition, on healthy 8–13 year-old children. This study replicates and extends previous studies describing positive effects of WBV on cognition in healthy adults [ 1 , 13 , 15 ]. Based on previous findings, it is expected that cognitive functioning improves in healthy children when assessed immediately following WBV treatment.…”
Section: Introductionsupporting
confidence: 90%
“…First, Fuermaier and colleagues [ 1 ] showed that not only in healthy individuals but also in individuals with ADHD, inhibition improved when assessed shortly after receiving WBV treatments of two minutes. Second, Fuermaier and colleagues demonstrated longer-lasting effects (at least 16 hours) of WBV on several neuropsychological measures of attention and executive functions in a case report of an adult with ADHD [ 15 ]. Since WBV appears to specifically improve inhibition and attention which are both functions that are often impaired in patients with ADHD [ 16 ], WBV could be considered as a potentially new, effective and safe treatment option for ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in older adults and a young adult with ADHD effects of WBV on cognitive performance after respectively five weeks and ten days of stimulation were found [14,39]. The fact that we did not find improved cognitive functioning in the current population after six weeks of passive exercise may be explained by Another explanation for inconclusive results in cognitive function may be the fact that quantifying cognitive function is challenging in this population.…”
Section: Secondary Outcome Measures Cognitive-and Physical Functioncontrasting
confidence: 56%
“…However, in studies that employed (multi)sensory stimulation interventions such as 'snoezelen', video or music interventions, improvements in alertness and happiness, increased social behavior, and a reduction in behavioral disturbances as well agitated behavior of patients with dementia were found [6][7][8]. Additionally, mild vibrations (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), as provided during WBV and TMSim + WBV, can be beneficial for physical performance and cognitive functioning. Multiple studies reported increased muscle strength, mobility, balance and lower blood pressure after WBV [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies used task‐irrelevant sensory stimulations, which were found to have beneficial effects on clinical populations. For example, whole‐body vibration therapy (WBV), applied by sitting on a chair mounted on a vibrating platform, was found to improve attention and cognitive performance in an adult ADHD patient [Fuermaier, Tucha, & Koerts, ], and other clinical patient (Madou & Cronin, ). We believe that WBV combines the stimulation of both vestibular and proprioceptive receptors (and perhaps auditory and visual stimulations as well).…”
Section: Discussionmentioning
confidence: 99%